2016
DOI: 10.1088/0031-9155/61/6/2532
|View full text |Cite
|
Sign up to set email alerts
|

Biologically effective dose in fractionated molecular radiotherapy—application to treatment of neuroblastoma with131I-mIBG

Abstract: In this work, the biologically effective dose (BED) is investigated for fractionated molecular radiotherapy (MRT). A formula for the Lea–Catcheside G-factor is derived which takes the possibility of combinations of sub-lethal damage due to radiation from different administrations of activity into account. In contrast to the previous formula, the new G-factor has an explicit dependence on the time interval between administrations. The BED of tumour and liver is analysed in MRT of neuroblastoma with 131I-mIBG, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The BED expression has been extended to the MIRD schema and applied to organs at risk such as the red marrow and kidneys [58,59]. BED expressions were derived for fractionated treatments, which for fractions separated by long time intervals with respect to the effective halflife result in the sum of the BED from each fraction [96,97].…”
Section: Factors That Modify the Radiobiological Responsementioning
confidence: 99%
“…The BED expression has been extended to the MIRD schema and applied to organs at risk such as the red marrow and kidneys [58,59]. BED expressions were derived for fractionated treatments, which for fractions separated by long time intervals with respect to the effective halflife result in the sum of the BED from each fraction [96,97].…”
Section: Factors That Modify the Radiobiological Responsementioning
confidence: 99%
“…Furthermore, the absorbed dose might not be the ideal quantity to consider. The transition from the absorbed dose as main parameter to start with to radiobiological quantities and models able to take into account DNA damage and repair mechanisms, the number and frequency of treatment cycles and other radiobiological effects, is thus a further challenge [110].…”
Section: Discussionmentioning
confidence: 99%
“…Some centres may have legal restrictions in the maximum activity to be administered, which may force them to decrease the total activity to be administered if the treatment is given in two fractions. A recent study [52] analysed from a radiobiological viewpoint the benefits of different schedules with more fractions without decreasing the total activity to be administered. The study demonstrated that although the tumour BED could decrease by up to 12% when delivering 4 Gy whole-body doses over more than two fractions, this decrease was modest compared to reducing the overall administered activity.…”
Section: Discussionmentioning
confidence: 99%